Ultrasound assisted one pot synthesis of imidazole derivatives using diethyl bromophosphate as an oxidant - Nagargoje, Deepak; Mandhane, Priyanka; Shingote, Savita; Badadhe, Pravin; Gill, Charansingh H. (Ultrasonics Sonochemistry, 2012)
A one pot, three-component condensation of benzoin/benzyl, an aldehyde, and ammonium acetate using diethyl bromophosphate as a mild oxidant is achieved to form trisubstituted imidazole compounds. Under ultrasound irradiation, a smooth condensation occurs to get the 2, 4, 5-triaryl-1H-imidazole compounds in good to excellent yields. The study explores the scope and limitation of diethyl bromophosphate as an oxidant and suggests advantages, viz., simplicity of operation, reduction in time, and an increase in product yields. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Diethyl bromophosphate (DEP); Imidazole; One pot synthesis; Ultrasound

Synthesis and crystal structures of Mn(II) and Co(II) complexes as catalysts for oxidation of cyclohexanone - Tella, Adedibu C.; Isaac, Aaron Y.; Clayton, Hadley S.; Ogunlaja, Adeniyi S.; Venugopalan, Aswathy T.; Prabu, Marimuthu; Thirumalaiswamy, Raja (Inorganics, 2022)
The global demand on adipic usage in the production of plasticizers and synthetic polyamide is increasing. In line with the search for an efficient and energy-conserving way to isolate adipic acid (AA) in good yields, this paper introduces the oxidization of cyclohexanone utilizing two new coordination compounds, [Mn(2,6-pydc)(2)](imi) (1) and [Co(H(2)pza)(2)(H2O)(2)(NO3)].NO3 (2), as catalysts. Compounds 1 and 2 were synthesized by room temperature and refluxing methods, and characterized by spectral analyses (IR and UV-Vis.), SEM, BET, TGA, elemental, and X-ray crystallography. The single crystal structure of compound 1 revealed that pyridinedicarboxylate (2,6-pydc) and imidazole (imi) moieties were coordinated to the Mn(II) atom through imine nitrogen and deprotonated oxygen atoms, to form an undistorted octahedral coordination geometry with the N2O4 donor set. The axial and equatorial planes containing O2, O4, O5, and O7 atoms were from two adjacent 2,6-pydc ligands which formed the unidendate donor ligand; imi, on the other hand, acted as a bidendate donor ligand. For compound 2, the Co(II) atom was being coordinated by two pyrazinamide (H(2)pza) moieties, which acted as an unidendate donor ligand; two water molecules occupying the axial position, and one nitrate molecule occupying the apical position, were within the coordination sphere; a nitrate molecule was disordered outside the coordination sphere. The distance, 4.658 angstrom, between the Co1 atom and the N8 atom of the uncoordinated nitrate molecule, was within the range reported elsewhere. Cyclohexanone peroxidation experiments revealed that compound 1 exhibited unique catalytic performance by giving a 72.8% yield in adipic acid, in comparison to the 71.3% yield obtained with compound 2. The yields in AA were maintained by way of recyclability evaluation. The reaction kinetics of compound 2 gave less activation energy, E-a 2938 J mol(-1), while the thermodynamic parameters indicated that the chemical reactivity of cyclohexanone on the active surfaces of compounds 1 and 2 was via monolayer physisorption.
Keywords: cobalt; Complexes; cyclohexanone; Imidazole; managanese; Oxidation; pyrazinamide; pyridinedicarboxylate

Mitigating dendrite formation on a Zn electrode in aqueous zinc chloride by the competitive surface chemistry of an imidazole additive - Rana, Ashutosh; Thakare, Anup; Kumar, Nikhil; Mukherjee, Buddhadev; Torris, Arun; Das, Bidisa; Ogale, Satishchandra; Banerjee, Abhik (ACS Applied Materials and Interfaces, 2023)
Electrochemical energy storage systems are critical in several ways for a smooth transition from nonrenewable to renewable energy sources. Zn-based batteries are one of the promising alternatives to the existing state-of-the-art Li-ion battery technology, since Li-ion batteries pose significant drawbacks in terms of safety and cost-effectiveness. Zn (with a reduction potential of -0.76 V vs SHE) has a significantly higher theoretical volumetric capacity (5851 mAh/cm3) than Li (2061 mAh/cm3), and it is certainly far less expensive, safer, and more earth-abundant. The formation of dendrites, hydrogen evolution, and the formation of a ZnO passivation layer on the Zn anode are the primary challenges in the development and deployment of rechargeable zinc batteries. In this work, we examine the role of imidazole as an electrolyte additive in 2 M ZnCl2 to prevent dendrite formation during zinc electrodeposition via experimental (kinetics and imaging) and theoretical density functional theory (DFT) studies. To characterize the efficacy and to identify the appropriate concentration of imidazole, linear sweep voltammetry (LSV) and chronoamperometry (CA) are performed with in situ monitoring of the electrodeposited zinc. The addition of 0.025 wt % imidazole to 2 M ZnCl2 increases the cycle life of Zn-symmetric cells cycled at 1 mA/cm2 for 60 min of plating and stripping dramatically from 90 to 240 h. A higher value of the nucleation overpotential is noted in the presence of imidazole, which suggests that imidazole is adsorbed at a competitively faster rate on the surface of zinc, thereby suppressing the zinc electrodeposition kinetics and the formation. X-ray tomography reveals that a short circuit caused by dendrite formation is the main plausible failure mechanism of Zn symmetric cells. It is observed that the electrodeposition of zinc is more homogeneous in the presence of imidazole, and its presence in the electrolyte also inhibits the production of a passivating coating (ZnO) on the Zn surface, thereby preventing corrosion. DFT calculations conform well with the stated experimental observations.
Keywords: dendrite; Density functional theory; exchange current density; Imidazole; X-ray computed tomography; zinc metal electrodeposition

Zwitterionic tetrastanna(II) cyclic crown - Sahoo, Padmini; Chibde, Purva; Das, Satyabrata; Banerjee, Subhrashis; Mali, Bhupendra P.; Vanka, Kumar; Gonnade, Rajesh G.; Yildiz, Cem. B.; Majumdar, Moumita (European Journal of Inorganic Chemistry, 2023)
A 12-membered zwitterionic tetrastanna(II) cycle 1 having a crown ether-like topology has been isolated from the deprotonation of 1,1 & PRIME;-methylenediimidazole (B) with two equivalents of Sn[N(SiMe3)(2)](2) (A). The solid-state structure and NMR analysis confirms the tetrastanna(II) cycle 1 to be comprised of two stannate(II) and two stannyliumylidene ion pairs in alternating positions of the heterocycle. Computational analysis shows greater nucleophilicity at the proximally located stannate(II) centers. Nonetheless, the tetrastanna(II) cycle 1 remains poorly reactive due to engagement of Sn-II lone pair electrons in intramolecular donor-acceptor interactions. Simple deprotonation reaction between Sn[N(SiMe3)(2)](2) (A) and N-(diisopropylphenyl)imidazole (C) in equimolar ratio has led to a stannylene 2, involving the formation of a Sn-C covalent bond with the anionic imidazol-2-yl carbon center along with the release of NH(SiMe3)(2). Compound 2 exists as a dimer, where the unsubstituted ring nitrogen atom coordinated intermolecularly to the other stannylene center.
Keywords: Deprotonation; Imidazole; Macrocycle; Sn-II cation; stannylene